2017
DOI: 10.1177/1059840517747974
|View full text |Cite
|
Sign up to set email alerts
|

Educators’ Experiences Identifying Pain Among Students in Special Education Settings

Abstract: If special educators cannot identify pain in students with intellectual disability (ID), students cannot be referred to the school nurse for assessment and management. The purpose of this study was to examine how special educators identify pain in the school setting. Twenty-four special educators participated in focus groups aiming to (1) identify educators' observations and perceptions of pain in students with ID and (2) determine the decision-making processes educators use to determine the need for student p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Working as an effective member of an interprofessional group is an important skill for all members of a student team. To the same degree that teachers can provide valuable input to school nurses about student health (Quinn & Serna, 2019), school nurses can make valuable contributions as school teams create student accommodation plans. School nurse respondents reported that collaboration on interprofessional teams for at-risk students was important (importance rating 3.46) and performed often (frequency rating 3.0).…”
Section: Discussionmentioning
confidence: 99%
“…Working as an effective member of an interprofessional group is an important skill for all members of a student team. To the same degree that teachers can provide valuable input to school nurses about student health (Quinn & Serna, 2019), school nurses can make valuable contributions as school teams create student accommodation plans. School nurse respondents reported that collaboration on interprofessional teams for at-risk students was important (importance rating 3.46) and performed often (frequency rating 3.0).…”
Section: Discussionmentioning
confidence: 99%
“…There is a need for education for providers regarding evaluating and treating pain in children with MC. 15,[33][34][35][36] Pain education, in general, is limited for health care providers across specialties and disciplines. [37][38][39][40][41] Supervising clinicians may use the GRASP to help trainees gain knowledge and skills in identifying sources of pain in children with MC.…”
Section: Discussionmentioning
confidence: 99%
“…Their caregivers spend every day with them, almost doing a continuous assessment to meet the child's needs. Caregivers can include parents, teachers, and other professionals who often have an intuitive sense about a child's pain and will instinctively know where the pain is Quinn & Serna, 2019). By gaining parental input, nurses will be able to adequately manage the pain of their students.…”
Section: Pain Assessment Solutionsmentioning
confidence: 99%